2016
DOI: 10.1177/1534735415624141
|View full text |Cite
|
Sign up to set email alerts
|

Examining Mediators and Moderators of Yoga for Women With Breast Cancer Undergoing Radiotherapy

Abstract: Hypothesis This study examines moderators and mediators of a yoga intervention targeting quality-of-life (QOL) outcomes in women with breast cancer receiving radiotherapy. Methods Women undergoing 6 weeks of radiotherapy were randomized to a yoga (YG; n = 53) or stretching (ST; n = 56) intervention or a waitlist control group (WL; n = 54). Depressive symptoms and sleep disturbances were measured at baseline. Mediator (posttraumatic stress symptoms, benefit finding, and cortisol slope) and outcome (36-item Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 62 publications
(84 reference statements)
0
73
0
2
Order By: Relevance
“…In addition, the PCS physical functioning subscale also revealed a statistically and clinically significant difference for yoga compared with the active‐stretching control group at the primary time point. Moderator analyses further indicated that the efficacy of yoga for improving the MCS score was more pronounced for women with elevated sleep disturbances and depressive symptoms at the start of radiotherapy …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the PCS physical functioning subscale also revealed a statistically and clinically significant difference for yoga compared with the active‐stretching control group at the primary time point. Moderator analyses further indicated that the efficacy of yoga for improving the MCS score was more pronounced for women with elevated sleep disturbances and depressive symptoms at the start of radiotherapy …”
Section: Resultsmentioning
confidence: 99%
“…Moderator analyses further indicated that the efficacy of yoga for improving the MCS score was more pronounced for women with elevated sleep disturbances and depressive symptoms at the start of radiotherapy. 38 Another study by Chaoul and colleagues (2018) stated that the primary outcomes were self-reported sleep disturbances (Pittsburgh Sleep Quality Index) and fatigue (Brief Fatigue Inventory) 1 week after the intervention. 45 In their study, no group differences were noted in total sleep disturbances or fatigue levels over time.…”
Section: During Cancer Treatmentmentioning
confidence: 99%
“…In another yoga versus exercise study no group differences were noted on decreased body fat [122]. In a yoga versus a stretching versus a waitlist control group, at the end of the six treatments the yoga group showed the greatest reduction in depressive symptoms and sleep problems [123]. And in another yoga versus stretching versus waitlist control group study, at the end of the six week treatment period (3 times a week) and at a six month follow-up period the yoga group showed greater increases in physical functioning and greater decreases in cortisol levels [124].…”
Section: Breast Cancermentioning
confidence: 99%
“…Of the 19 RCTs that were included in Table 1, six RCTs included healthy participants [56][57][58][59][60][61], including nurses [57], teachers [58], and women in the menopausal transition period or postmenopausal period [56,[59][60][61]. Other 13 RCTs included breast cancer patients undergoing treatment [62][63][64][65], breast cancer patients who had completed treatment [13,[66][67][68], type 2 diabetes mellitus patients [69], fibromyalgia patients [70], knee osteoarthritis patients [71], restless leg syndrome patients [72], and patients experiencing dysfunctional uterine bleeding [73].…”
Section: Study and Participant Characteristicsmentioning
confidence: 99%
“…Of the 19 included studies in Table 1, three reported using Iyengar Yoga [13,60,72]; two reported using Hatha Yoga [68,71]; two reported using Tibetan Yoga [61,64]; two reported using Restorative Yoga [66,67]; one reported using Vini Yoga [56]; one reported using Yoga Relaxation with MindSound Resonance Technique [58]; one reported using yoga breathing exercise in warm water [70]; and only seven RCTs revealed yoga programs with postures, breathing, relaxation or mediation, without defining the specific style of yoga [57,59,62,63,65,69,73]. All RCTs included yoga postures in their yoga intervention; 16 RCTs included yoga breathing; 15 RCTs included yoga relaxation; 12 RCTs included meditation; and 7 RCTs included all contents with postures, breathing, relaxation, and meditation for the yoga intervention group [57,59,63,65,67,69,73]. The duration of yoga interventions ranged from 1 week to 24 weeks, with a median of 10 weeks; the frequency of yoga interventions ranged from one to five weekly sessions of 45 to 120 min.…”
Section: Intervention Characteristicsmentioning
confidence: 99%